Formulation and Characterization of Solid Self Nano Emulsifying Drug Delivery System (S-SNEDDS) Loading Curcuma xanthorrhiza Extract - Yandi Syukri; Yuvina Seran; Hannie Fitriani; Arba Pramundita Ramadhani; Muhammad Taher (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Curcuma xanthorrhiza has an active component xanthorrhizol that is poorly soluble in water, resulting in limited absorption and bioavailability. Liquid Self Nano Emulsifying Drug Delivery System (SNEDDS) dosage formulations can improve its solubility and absorption due to its small particle size. Solid SNEDDS technology significantly overcomes some of problems in liquid SNEDDS preparations to improve the stability of liquid formulations. This study aims to formulate and characterize Curcuma xanthorrhiza S-SNEDDS preparation. SNEDDS was characterized by particle size and thermodynamic tests. Method of making S-SNEDDS uses two ways, absorption of porous compounds and spray drying. S-SNEDDS were characterized by testing infrared spectra, X-ray diffraction, scanning electron microscopy, microbial contamination and particle flow properties. Optimal S-SNEDDS formulation with 2 formulas namely F7 and F11 mannitol carrier. FTIR testing showed no interacting compounds. SEM and X-ray diffraction testing of F7 showed that the preparation was semicrystalline. While F11 described the preparation as much more crystalline due to the high content of mannitol. The microbial contamination test detected no microorganism compounds. In addition, the particle flow properties obtained a result of 02.53 seconds with a height of 24.95 mm. It is concluded that the S-SNEDDS formula F7 of Curcuma xanthorrhiza has semicrystalline preparation criteria.